Enhanced light harvesting and charge separation over wormhole mesoporous TiO2−X nanocrystallites towards efficient hydrogen generation. Issue 5 (8th April 2019) - Negi, Sanjay Singh
Abstract : Improved visible light absorption by meso-TiO2− X materials compared to TiO2 for enhanced solar light harvesting. Abstract : Here meso-TiO2− X materials with combined visible light absorption, high surface area, an anatase–rutile heterojunction, and electrically interconnected nanocrystallites in a wormhole mesoporous framework are achieved. Meso-TiO2− X materials were prepared by solution combustion synthesis (SCS), followed by hydrogenation at higher temperatures. The materials are thoroughly characterised by various physicochemical techniques. A small band gap (2.8 eV), type IV-H2 mesoporosity with a biphasic heterojunction, and small pore depths (10 nm) in a wormhole mesoporous framework are observed with 35AP. Photocatalytic water splitting for hydrogen production and photocurrent generation were carried out with meso-TiO2− X materials under simulated sunlight. A six-fold increase in activity under AM 1.5G irradiation was observed, which is attributed to the generated mid-gap states which lead to band gap reduction, improved optical absorption in the visible and infrared light region resulting in higher charge carrier density. The presence of a biphasic heterojunction between the (1 0 1) anatase and (1 1 0) rutile facets assists in effective charge separation. A low charge diffusional constraint associated with wormhole mesoporosity helps in facile charge transport to the surface for improved charge utilisation in redox reactions.